The body and sound as stimulators of interactive processes in young people with special educational needs - Lamounier, Slavisa (2019)
Introduction: Inserted in the development of a digital musical instrument, the Digital Sock, we present in this document the results obtained from the analysis of the psycho-pedagogical interactive cycle in which we investigate the instrument as a sound stimulation tool in interactive processes between body-instrument-environment. Objetives: Analysis of the psych pedagogical interaction cycle that investigates the relationship between body and sound, with the new instrument, the Digital Sock, as a stimulating device for communicational processes. Methods: The methodology used for this investigation was action research. In the first phase, we conducted a psychopedagogical intervention with young people in Special Education. In the second phase, we conducted a Case Study with a young man diagnosed with Autism Spectrum Disorder. For data collection we used audiovisual media and field diary, focused interview, participant observation and document analysis. For the interpretation of the data we performed the discourse analysis and the content analysis. The acting model used during the two phases of practical intervention prioritized the integration of music and body movement (Dalcroze, 1920; Pederiva, 2004; Santiago, 2008; Storolli, 2011); the formation of the scenic gesture (Laban, 1978; Katz, 2005; Miller, 2007; Greiner & Amorim, 2010; Miller, 2012; Amaral, 2015; Roquet, 2017); ludic practice (Lapierre, 1982; Fonseca, 2001; Acouturier & Lapierre, 2004; Vieira, Batista & Lapierre, 2005); creative improvisation (Nordoff & Robins, 1959; Bruscia, 1999) and the belief that sound and music enable peer communication (Benenzon, 1981; Whipple, 2004). Results: The body-sound relationship as a means of expression has shown to be able to stimulate creative processes and the development of critical and reflexive thinking. All the activities developed during the meetings prioritized the body-sound relationship. The analysis of the narratives showed that the message propagated by the sock (the sonority) was understood as a reaction to the sound heard during the exercise (with individual encoding and decoding) and expressed through the eyes of the hands, facial expression and body balance-subtle movements, more visible than the broad movements. Conclusions: The interpretation of the data led us to conclude that Digital Sock, perceived as a psychopedagogical tool for sound and gestural stimulation, favours the development of scenic-musical narratives in young people with Special Educational Needs.